Influence analysis of director’s elements on the circular Yagi disc antenna performance at 1.8 GHz - Shamsudin, Mustaqim Hakimi; Ibrahim, Imran Mohd; Al-Gburi, Ahmed Jamal Abdullah; Purnamirza, Teddy (International Journal of Electrical and Computer Engineering (IJECE), 2023)
This paper aims to investigate and design a Yagi disc antenna with a variable number of director elements for Band 3 in fourth-generation long term evolution (4G LTE) mobile applications. The array technique was introduced by increasing the number of director elements to achieve superior results and better performance, such as higher gain and lower return loss. Initially, the simulated results of return loss and gain with one director element were -19.02 dB and 8.51 dBi, respectively. Then, by increasing the number of directors to three and five elements, the antenna’s performance improved significantly from -32.44 to -42.68 dB for return loss and from 8.51 to 11.17 dBi for gain, respectively. The simulated circular Yagi disc antenna provided a response in the range of 1.78 to 1.82 GHz. Therefore, a model was fabricated and tested to validate the antenna design. The measured results matched well with the simulated ones. By increasing the number of director elements, the measurement results of gain and return loss at a frequency of 1.8 GHz also showed improvement from 7.70 to 11.09 dBi and from -27.31 to -32.91 dB, respectively. Meanwhile, the measured antenna provided a wider bandwidth in the range of 1.72-1.82 GHz.